Platelets derived citrullinated proteins and microparticles are potential autoantibodies ACPA targets in RA patients - Xu, Minjie; Du, Rong; Xing, Wenping; Chen, Xueting; Wan, Jian; Wang, Shengqing; Xiong, Li; Nandakumar, Kutty Selva; Holmdahl, Rikard; Geng, Hui (Frontiers in Immunology, 2023)
Citrullinated neoepitopes have emerged as key triggers of autoantibodies anti-citrullinated protein antibodies (ACPA) synthesis in rheumatoid arthritis (RA) patients. Apart from their critical role in homeostasis and thrombosis, platelets have a significant contribution to inflammation as well. Although anuclear in nature, platelets have an intricate post-translational modification machinery. Till now, citrullination in platelets and its contribution to trigger autoantibodies ACPA production in RA is an unexplored research direction. Herein, we investigated the expression of peptidylarginine deiminase (PAD) enzymes and citrullinated proteins/peptides in the human platelets and platelet derived microparticles (PDP). Both PAD4 mRNA and protein, but not the other PAD isoforms, are detectable in the human platelets. With a strict filtering criterion,108 citrullination sites present on 76 proteins were identified in the human platelets, and 55 citrullinated modifications present on 37 different proteins were detected in the PDPs. Among them, some are well-known citrullinated autoantigens associated with RA. Citrullinated forms of thrombospondin-1, β-actin, and platelet factor-4 (also known as CXCL4) are highly immunogenic and bound by autoantibodies ACPA. Furthermore, ACPA from RA sera and synovial fluids recognized citrullinated proteins from platelets and significantly activated them as evidenced by P-selectin upregulation and sCD40 L secretion. These results clearly demonstrate the presence of citrullinated autoantigens in platelets and PDPs, thus could serve as potential targets of ACPA in RA.